Ullmann's Encyclopedia of Industrial Chemistry 2001
DOI: 10.1002/14356007.a21_075
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Group Metals and Compounds

Abstract: The article contains sections titled: 1. History 2. Properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 108 publications
0
41
0
Order By: Relevance
“…Platinum group metals and their complexes have been used in many practical applications, because of their excellent catalytic activities. 65 However, electrical properties and other practical features are not well known apart from high electrical conductivity and robust corrosion resistance. Recent studies of Ir and Os oxides have shown that the significant SOC and extended 5d orbitals in the oxide produce outstanding electric and magnetic properties as found in Slater insulators, 19,66 Dirac-Mott insulators, 60,62 and ferroelectric metals.…”
Section: Resultsmentioning
confidence: 99%
“…Platinum group metals and their complexes have been used in many practical applications, because of their excellent catalytic activities. 65 However, electrical properties and other practical features are not well known apart from high electrical conductivity and robust corrosion resistance. Recent studies of Ir and Os oxides have shown that the significant SOC and extended 5d orbitals in the oxide produce outstanding electric and magnetic properties as found in Slater insulators, 19,66 Dirac-Mott insulators, 60,62 and ferroelectric metals.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike any other PGE, Rh can be dissolved in boiling HBr/Br 2 . The metal can also be dissolved by melting with potassium or sodium hydrogensulfate, while Pt, Ir, and Ru remain unaffected (Renner et al, 2001). Rhodium is the only monoisotopic PGE, making it inaccessible for isotope dilution mass spectrometry.…”
Section: Propertiesmentioning
confidence: 99%
“…The content of PGMs in nickel deposits varies depending on the type of the mineral deposit. In South Africa, the average platinum grade is around 27 g per tonne, whereas in Russia the average PGM content is 15 g per tonne in nickel sulphide ore deposits [86]. Taking as an average 20 g per tonne and the total world nickel production from sulphide ore for 2010 of 870 000 tonnes, it seems that 17 tonnes of PGMs were potentially available for recovery [87].…”
Section: (V) Nickel By-products: Cobalt and Platinum Group Of Metalsmentioning
confidence: 99%